The Effect of Physical Exercise on Muscle Strength in Chronic Rental Failure Patients during Hemodialysis: Article Review - Anggraeni, Fitria Rizky; Ardiansyah, Faizin; Ayuninggar, Lintang; Fadjriyah, Mandha Noor; Krisdeana, Afinda; Dewangga, Mahendra Wahyu (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Chronic kidney failure is a condition in which kidney tissue has progressively decreased function so that it is unable to maintain fluid balance in the body and requires therapy, namely hemodialysis. Improving physical work capacity and reducing functional limitations of muscle strength can be done through regular physical exercise in patients with chronic kidney failure after undergoing hemodialysis. Therefore it is necessary to conduct a systematic review study to determine the effect of physical exercise on chronic kidney failure patients. There are 5 articles used in this research. Based on the articles obtained, it can be concluded that physical exercise in patients with chronic kidney failure during the hemodialysis period greatly influences muscle strength.